Coronary Artery Rupture Caused by Stent Infection. Issue 14 (7th April 2015) - Roubelakis, Apostolos; Rawlins, John; Baliulis, Giedrius; Olsen, Sally; Corbett, Simon; Kaarne, Markku; Curzen, Nick
<x xml:space="preserve">Abstract</x> Supplemental Digital Content is available in the text.